PENGARUH KOMITMEN ORGANISASIONAL, LINGKUNGAN KERJA, DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION - URFAH, NADIA; WIDAYATI, NURTI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to determine the effect of organizational commitment, work environment, and job satisfaction on the turnover intention.This research was conducted at PT XYZ, by taking 111 employees as research samples using purposive sampling technique. Collecting data using observation methods and questionnaires. The data analysis technique used is multiple regression analysis. Based on the study conduct, the results of the analysis showed that organizational commitment has an effect on turnover intention. While work environment and job satisfaction had no effect on turnover intention.